Sistem Pakar Untuk Mendiagnosa Penyakit Skizofrenia Dengan Metode Forward Chaining (Studi Kasus : RS Jiwa Surakarta) - Kurniawan, Dwi Cahyo; , Dr. Heru Supriyono, M.Sc (2016)
Health is a precious thing for human life. Not only physical health, mental health should also get the same attention. Schizophrenia is a psychiatric disorder that affects brain function, cognitive, emotional and behavioral. In the process of diagnosis of schizophrenia, your doctor will collect data about the symptoms that indicate patients with schizophrenia. But the barriers are doctors or medical professionals in the field of schizophrenia are not always standby at the hospital. This is the background to design and create web-based expert system to diagnose schizophrenia with forward chaining method. Forward chaining is a reasoning that starts from the facts to the conclusion. This web-based expert system using PHP programming language and stored in a MySQL database. Results of the study is a web-based application that can diagnose schizophrenia. Testing the system using questionnaires with respondents doctors, paramedics and the patient's parents. Based on a questionnaire given highest percentage of 87% related to the function of the system can help diagnose a patient while the paramedics in the lowest 83% of the design view.